Urinary ketone body loss leads to degeneration of brain white matter in elderly SLC5A8-deficient mice. Issue 8 (August 2020) - Suissa, Laurent; Flachon, Virginie; Guigonis, Jean-Marie; Olivieri, Charles-Vivien; Burel-Vandenbos, Fanny; Guglielmi, Julien; Ambrosetti, Damien; Gérard, Matthieu; Franken, Philippe; Darcourt, Jacques; Pellerin, Luc; Pourcher, Thierry; et al.
SLC5A8 is a sodium-coupled monocarboxylate and ketone transporter expressed in various epithelial cells. A putative role of SLC5A8 in neuroenergetics has been also hypothesized. To clarify this issue, we studied the cerebral phenotype of SLC5A8-deficient mice during aging. Elderly SLC5A8-deficient mice presented diffuse leukoencephalopathy characterized by intramyelinic oedema without demyelination suggesting chronic energetic crisis. Hypo-metabolism in the white matter of elderly SLC5A8-deficient mice was found using 99m Tc-hexamethylpropyleneamine oxime (HMPAO) single-photon emission CT (SPECT). Since the SLC5A8 protein could not be detected in the mouse brain, it was hypothesized that the leukoencephalopathy of aging SLC5A8-deficient mice was caused by the absence of slc5a8 expression in a peripheral organ, i.e. the kidney, where SLC5A8 is strongly expressed. A hyper-excretion of the ketone β-hydroxybutyrate (BHB) in the urine of SLC5A8-deficient mice was observed and showed that SLC5A8-deficient mice suffered a cerebral BHB insufficiency. Elderly SLC5A8-deficient mice also presented altered glucose metabolism. We propose that the continuous renal loss of BHB leads to a chronic energetic deficiency in the brain of elderly SLC5A8-deficient mice who are unable to counterbalance their glucose deficit. This study highlights the importance of alternative energetic substrates in neuroenergetics especially under conditions of restricted glucose availability.